Intervention Effect of Mindful Self-Compassion Training on Adolescents' Psychological Stress during the Pandemic - Min Dai; Guohua Liu (Tehran University of Medical Sciences, 2022)
Background: COVID-19 has been confirmed as a public health emergency and may give rise to adverse emotions such as anxiety and fear, and even stress reactions in serious cases. In a critical period of emotional development, adolescents experience more psychological stress fluctuations. Mindful self-compassion training is a simple and easy psychological assistance technology that has been recognized as effective, but it has not been applied to adolescents' psychological problems caused by the epidemic. Methods: From September 2021 to January 2022, adolescent volunteers were recruited in this study from four communities in Chongqing, China. A total of 107 adolescents volunteered to participate in this intervention experiment and were divided by the table of random numbers into 53 in the experiment group and 54 in the control group. The experiment group was intervened using mindful self-compassion training in combination with aerobic exercise for two months, while no intervention measures were taken in the control group. Stress Appraisal Measure, Profile of Mood States and Pittsburgh Sleep Quality Index were the scales adopted to evaluate the effect before and after the intervention. Results: The experimental group had significantly lower negative mood, stress, sleep scores than the control group (P < 0.001) and significantly higher differences before and after treatment than the control group (P < 0.001). Conclusion: The intervention in this study can effectively reduce the level of negative mood and stress in individuals, and improve their vitality and sleep quality and provides new insights for the implementation and improvement of psychological assistance technology.